Estimation of seismic behavior through static nonlinear analysis of an 8-story multifamily home, La Esperanza, Trujillo - Gutierrez Mendoza, Cesar Alexander; Villacorta Olivares, Denilson; Noriega Vidal, Eduardo Manuel; Martell Ortiz, Juan Carlos; Valdivieso Velarde, Alan Yordan; Rodriguez Beltran, Eduar Jose (LACCEI, 2024)
The general objective of the research is to estimate the seismic behavior through static nonlinear analysis of an 8-story multifamily home. Likewise, the type of research will be applied and its design will be non-experimental of a descriptive nature, in which We will propose a multi-family home located at Mz 2, Lt 19, Jerusalem Sector, Esperanza District, Trujillo Province, La Libertad, in which the structure was divided into two modules; thus finding that the point of maximum performance is found in life safety for an earthquake with a return time of 72 years in the direction of the X axis and functional in the direction of the Y axis, for earthquakes with a return time of 450 years and 975 years. were found in a state of collapse in both directions of analysis, likewise it was determined that modules 1 and 2 could not exceed a resistance of 656.3224 tonf in the capacity demand curve in the X direction, nor 1023.7692 tonf in the Y direction, being In this sense, where a greater amount of internal forces are developed in the structural elements, generating a greater concentration of plastic hinges in beams, being in accordance with the philosophy of ACE41-13 and FEMA 440.